Relationships between range access as monitored by radio frequency identification technology, fearfulness, and plumage damage in free-range laying hens. (23rd November 2015) - Hartcher, K. M.; Hickey, K. A.; Hemsworth, P. H.; Cronin, G. M.; Wilkinson, S. J.; Singh, M.
Abstract : Severe feather-pecking (SFP), a particularly injurious behaviour in laying hens (Gallus gallus domesticus), is thought to be negatively correlated with range use in free-range systems. In turn, range use is thought to be inversely associated with fearfulness, where fearful birds may be less likely to venture outside. However, very few experiments have investigated the proposed association between range use and fearfulness. This experiment investigated associations between range use (time spent outside), fearfulness, plumage damage, and BW. Two pens of 50 ISA Brown laying hens ( n =100) were fitted with radio frequency identification (RFID) transponders (contained within silicone leg rings) at 26 weeks of age. Data were then collected over 13 days. A total of 95% of birds accessed the outdoor run more than once per day. Birds spent an average duration of 6.1 h outside each day over 11 visits per bird per day (51.5 min per visit). The top 15 and bottom 15 range users ( n =30), as determined by the total time spent on the range over 13 days, were selected for study. These birds were tonic immobility (TI) tested at the end of the trial and were feather-scored and weighed after TI testing. Birds with longer TI durations spent less time outside ( P =0.01). Plumage damage was not associated with range use ( P =0.68). The small group sizes used in this experiment may have been conducive to the high numbers of birds utilising the outdoor range area. The RFID technology collected a large amount of data on range access in the tagged birds, and provides a potential means for quantitatively assessing range access in laying hens. The present findings indicate a negative association between fearfulness and range use. However, the proposed negative association between plumage damage and range use was not supported. The relationships between range use, fearfulness, and SFP warrant further research.